Pioneers of Capitalism and the Low Countries’ Paradox - Blondé, Bruno; Marx, Ive (TSEG - The Low Countries Journal of Social and Economic History, 2024)
In 2013, Maarten Prak and Jan Luiten Van Zanden published an all-encompassing synthesis on the economic history of the Netherlands following the “Polder-model-theory”, in itself a variant of the “Rhineland model”. In their opinion, relatively low levels of inequality, a consensus model, and a strong civil society were cornerstones that accounted for a different pathway to capitalism. This review engages hesitantly with this comparative perspective, especially in regard of the history of present-day Belgium.